Analyzing the distributional impact of selected reforms - Coudouel, Aline; Paternostro, Stefano; World Bank. (Washington, D.C. : World Bank, 2005)
Provides an overview of the specific issues arising in the analysis of the distributional impacts of policy and institutional reforms in selected sectors. Each chapter in these two volumes offers guidance on the selection of tools and techniques adapted to the reforms under scrutiny, and offers examples of applications of these approaches.
Includes bibliographical references.
oif 03/08/16, ijb 21/02/2019
Loan
Keywords: Poverty; Economic policy; Developing countries